China & the USA - Fouskas, Vassilis K. author. aut Link
XV, 94 p. 4 illus.
Keywords: This book examines the political economy of conflict between China, a rising power, and the USA, a declining one. It provides an informed analysis as to why China is the main beneficiary of neo-liberal globalisation, a project launched in the wake of the collapse of the Bretton Woods system in the late 1960s under the aegis of the USA. Why are Huawei and other Chinese high-tech giants targeted by the USA and its allies? What is the role of the state and the Chinese political system in the development of China’s political economy, as well as its globalisation? Does China’s global rise provide a viable and sustainable alternative to neo-liberal globalisation? Since American leaders view increasingly the rise of China as a threat, how likely is an armed conflict between China and the USA? This book answers these questions by using a wealth of empirical material and debating with many theoretical schools of thought, Marxist or otherwise. Vassilis K. Fouskas is Professor of international relations and Director of the Centre for the Study of States, Markets & People (STAMP) at the School of Business & Law, University of East London (UEL). He is the Founding Editor of the Journal of Balkan and Near Eastern Studies (Routledge/Taylor & Francis). Shampa Roy-Mukherjee is Senior Lecturer in Economics, Director of Impact & Innovation at the School of Business & Law, UEL, and a member of the Executive Board of STAMP. Qingan Huang is Senior Lecturer in Strategic Management at the School of Business & Law at UEL and Professor & Dean of International Business School, Guangdong University of Finance & Economics, China and a member of STAMP. Ejike Udeogu is Senior Lecturer in Economics and Acting Director of the MBA at the School of Business & Law, UEL, and a member of the Executive Board of STAMP.